Pengaruh Penurunan Harga TBS pada Kelapa Sawit dan Produktivitas terhadap Kesejahteraan Keluarga Karyawan pada PT. Pundi Lahan Khatulistiwa - Anwar, Misbahul; Sesario, Revi; Sutignya, Th. Candra Wasis Agung (Vokasi: Jurnal Publikasi Ilmiah, 2024)
This study discusses the effect of the decline in FFB prices on oil palm and productivity on employee family welfare at PT Pundi Lahan Khatulistiwa. This research uses a quantitative approach with a casual associative research category which means there is cause and effect. The objectives of this study are: 1) to determine the effect of the decline in FFB prices on oil palm and productivity simultaneously on the welfare of employee families at PT Pundi Lahan Khatulistiwa, 2) to determine the effect of the decline in FFB prices on oil palm partially on the welfare of employee families at PT Pundi Lahan Khatulistiwa, and 3) to determine the effect of productivity partially on the welfare of employee families at PT Pundi Lahan Khatulistiwa. A total of 100 people consisting of employees and their families were used as research samples determined by the Slovin formula. This research data is primary data obtained directly from the first source either from individuals or individuals such as the results of filling out questionnaires. The method used is multiple linear regression analysis assisted by IBM SPSS (Statistical Package for Social Science) software version 29.0. The results of the research conducted showed that: 1) the decline in FFB prices and productivity simultaneously (together) and significantly affect the welfare of employee families at PT Pundi Lahan Khatulistiwa, 2) the decline in FFB prices partially (alone) and significantly affect the welfare of employee families at PT Pundi Lahan Khatulistiwa, and 3) productivity partially (alone) and significantly affect the welfare of employee families at PT Pundi Lahan Khatulistiwa.